Comparison of Abdominal and Vaginal Hysterectomy: A Comparative Clinical Study at A Tertiary Hospital of Southern Part of Bangladesh (KYAMC Journal, 2024)
Background: Hysterectomy is indicated in several common gynecologic problems and is one of the commonly performed operations in many hospitals of Bangladesh. Though Hysterectomy is a reasonably safe operative procedure but at times minor to major complications may occur. Current study was undertaken to compare the feasibility and safety of abdominal hysterectomy (AH) and vaginal hysterectomy (VH) procedures in the treatment of benign uterine diseases, and to determine the outcomes of both procedures. Objectives: To compare outcomes of vaginal and abdominal hysterectomy procedures in women with benign gynaecological diseases. Materials and Methods: This was a prospective study of outcomes of consecutive patients who underwent AH or VH for benign gynaecological diseases. Patient characteristics before, during, and after the operations were reviewed. Patients were followed up for three months to evaluate postoperative complications. Results: This study included a total of 305 patients. 199 patients underwent AH and 106 patients underwent VH. Baseline characteristics were similar between the two groups. Mean operative time was 95.78±18.46 minutes for AH group and 76.26±19.24 minutes for VH group (p